BIOLOGICAL PATHOTYPING AND RAPD ANALYSIS OF ASCOCHYTA RABIEI, FROM VARIOUS CHICKPEA GROWING AREAS OF PAKISTAN - N. Sarwar; S. Ashfaq; K. P. Akhtar; F. F. Jamil (Journal of Animal and Plant Sciences, 2013)
Blight disease caused by the fungus Ascochyta rabiei is considered to be the major constraint to chickpea production. Twenty-one isolates of A. rabiei were obtained from blighted samples collected from major chickpea growing areas in Pakistan during 2006-08. Biological pathotyping on a set of chickpea differentials indicated that four isolates were highly virulent; two were less virulent, while rest of the isolates was moderately virulent. RAPD assay was used to investigate the genetic diversity among the isolates. Twenty primers with random nucleotide sequences were tested. A total of 49 bands were polymorphic. Dendrogram constructed from RAPD data indicated that there was a high genetic variability among the isolates collected from different locations and were grouped into three main clusters.
Keywords: Ascochyta rabiei; blight; chickpea; DNA; Pathotypes; Genotyping